2019
DOI: 10.24843/ach.2019.v06.i01.p01
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Keinginan Perpindahan Fasilitas Kesehatan Tingkat Pertama Pada Peserta JKN Mandiri Di Kota Denpasar Tahun 2017

Abstract: ABSTRAK Keinginan pindah fasilitas kesehatan tingkat pertama merupakan salah satu bentuk ketidakpuasan pasien serta akan berdampak pada loyalitas pasien dalam memanfaatkan pelayanan kesehatan. Pada tahun 2016, terjadi peningkatan yang signifikan pada peserta JKN Mandiri di Kota Denpasar yang melakukan perpindahan FKTP yaitu di bulan Juni sebanyak 453 orang dan menjadi 504 orang pada bulan November 2016. Berdasarkan hasil wawancara dengan pihak BPJS Kesehatan Cabang Denpasar didapatkan data mengenai keluh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Primary Healthcare Services are integrated and accessible health services managed by clinicians responsible for carrying out individual health efforts, developing ongoing relationships with patients, and carrying out their practice within the family and community of all groups of people ( 28). This study's results are similar to those of previous studies, which found a relationship between access/(geography, transportation) and service utilization (20,(29)(30)(31)(32)(33) Other research states that respondents who live in urban areas with affordable access are related to the use of Prolanis. There are accessibility gaps in visiting routines, treatment appropriateness, and disease control based on the type of FKTP and place of residence (34).…”
Section: Discussionsupporting
confidence: 88%
“…Primary Healthcare Services are integrated and accessible health services managed by clinicians responsible for carrying out individual health efforts, developing ongoing relationships with patients, and carrying out their practice within the family and community of all groups of people ( 28). This study's results are similar to those of previous studies, which found a relationship between access/(geography, transportation) and service utilization (20,(29)(30)(31)(32)(33) Other research states that respondents who live in urban areas with affordable access are related to the use of Prolanis. There are accessibility gaps in visiting routines, treatment appropriateness, and disease control based on the type of FKTP and place of residence (34).…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with other studies which show that the comfort level, which consists of inadequate facilities during treatment and the lack of health human resources, is the reason for moving helath providers among independent NHI participants in Denpasar City. 11,13 This shows that the availability of human resources, facilities and capacity of service providers in the implementation of health services plays an important role as organizational goals can be implemented and health services can be carried out optimally. Primary health providers can increase their capacity including queues and waiting rooms, improve medical facilities which include examination rooms, pharmacies and basic laboratories and nonmedical facilities such as providing parking lots, maintaining physical buildings, and creating good air circulation and lighting.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in line with other studies which show that the failure of service interaction which includes the negative attitude of service workers who rush and convey information that is unclear is the reason for the switching of health providers among independent NHI participants in Denpasar City. 11,13 Therefore, it is important to make efforts to improve primary health providers based on the reason of sustainability of social relations, particularly by training health workers on how to communicate well, to display a friendly and polite attitude and provide appropriate information to patients which led to a sustainable positive relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are clinics with 51,717 participants with a ratio of 1:10,000, while there are individual practicing doctors with a very small number of only two participants. 3 Health facilities with high number of patients or unbalanced ratios have a tendency to bring about a decline in service quality, while primary care with a small number of participants will find it difficult to finance their health services. 4 A balance is required between the number of registered participants, operational adequacy and service quality through equal distribution of participant ratios throughout the primary care.…”
Section: Introductionmentioning
confidence: 99%